EVALUASI PELAKSANAAN SERTIFIKASI LAIK FUNGSI UNTUK GEDUNG PEMERINTAH DI KOTA SEMARANG - Bima Iskandar; Sarah Nur Eka Dini; Jati Utomo Dwi Hatmoko; Frida Kistiani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
The condition of buildings in the Semarang City, still needs to improve in reliability, this is because there are already several examples of building failures building before the design life, even up to swallow the casualties. From these problems the Government provides a solution in the form of SLF (certificate suitable function). SLF is a certificate issued by the local government to declare the reliability of a building, before the building is utilized / used. SLF was first listed on the Act No. 28 of 2002 regarding Building, Government Regulation No.36, and guidelines made by the Ministry of Public Works SLF 25 / PRT / 2007. Boundary problem in the research is the implementation of the SLF predicament for government-owned buildings in the city of Semarang by considering the function of government-owned buildings used for public purposes, while giving precedence to SLF buildings intended for public use such as: offices, schools and hospitals. For the implementation of the SLF field still constrained some major factors such as ownership of IMB is still minimal, as well as regulation of the mayors of Semarang on the SLF has not been established. To overcome the existing problems then use SWOT analysis. The use of SWOT aims to find an overview of the strategies of existing problems. In a SWOT analysis and supporting data needed SLF implementation constraints, which are then classified based on the strengths, weaknesses, opportunities and threats. After classifying the data and then given the weight of each. From the results incorporated into the subsequent weighting diagram SWOT analysis and obtained turnaround strategy. This strategy shows that the condition of SLF in Semarang is located on opportunities and weaknesses. Then, in solving problems SLF in the city of Semarang is by taking advantage of opportunities to minimize the weaknesses. One example of this strategy is effective immediately sanction available to the public in violation because of the passage of sanctions yet.